Burden of Care among Relatives of Patients with Schizophrenia - Sridevi R. G.; Talwar P., (International Journal of Management, Technology and Social Sciences (IJMTS), 2024)
Purpose: The purpose was to critically review the studies related to burden among relatives of patients with schizophrenic. Objective: The research is done to assess burden of care among relatives of patients with schizophrenia To Assess the Degree of Caregiver Burden To determine the factors contributing to burden Design/Methodology/Approach: A variety of secondary sources, such as journals, book chapters, conference proceedings, and other web pages, were used to compile the literature for this investigation. Every study has been thoroughly examined and summarized. It is also used to determine the gaps in the field and research objectives. Findings/Results: All recent study’s findings and constraints have been carefully considered. Each work's results have been closely scrutinized, and the reason for the gap has also been thoroughly investigated. Originality/Value: The goal of this manuscript is to review the pertinent research that has previously written. It also includes secondary information obtained from various online sources, such as websites, technical book chapters, conference papers, and research journals. The selected papers were all relevant to the intended work, up to date, and published by reliable publishers. A genuine attempt is made to select a research topic and carry out the investigation. Paper type: Review Paper.